Ursodeoxycholic acid in neonatal sepsis-associated cholestasis - Rina, Rita Mey; Oswari, Hanifah; Amalia, Pustika (Paediatrica Indonesiana, 2014)
Background Sepsis-associated cholestasis (SAC) is an intrahepaticÂ cholestasis caused by inflammatory cytokines. Patients withÂ this condition have poor prognoses. Antibiotics are the mainstayÂ of therapy, however, other adjuvant therapies, such as ursodeoxycholicÂ acid (UDCA), have not been well established. Objective To assess the effect ofUDCA for treatment ofneonatalÂ sepsis-associated cholestasis. Methods We performed a randomized, double-blind, controlledÂ trial in 3 7 neonates who were diagnosed with sepsis-associatedÂ cholestasis in the Neonatal Care Unit of Cipto MangunkusumoÂ Hospital. Subjects were divided into two groups, with 19 neonatesÂ randomly allocated to the intervention group (received UDCA atÂ 30 tngikg/day divided into 3 doses for 7 days) and 18 neonates toÂ the control group (received placebo) . After 7 days of treatment, weÂ evaluated the subjects’ liver function parameters and performed a survival analysis. Results Liver function parameter improvements at day 7 were notÂ significantly different between the UDCA group and the controlÂ group, including for mean decrease of total bilirubin (TB) levels [2.2Â (SD 2.9) mg/dL vs 1.7 (SD 4.6) mg/dL; P=0.080), mean decreaseÂ of direct bilirubin (DB) levels [1.1 (SD 2.3) mg/dL vs 0.6 (SD 3.6)Â mg/dL; P=0.080), median indirect bilirubin (lB) levels [0.4 (rangeÂ 0.1- 5.6) mg/dL vs 0.9 (range 0.1-4.1) mg/dL; P=0.358) , meanÂ decrease of alanine aminotransferase (ALT) levels [0.5 (-80.0 - 21.0) U/L vs -2.0 (ranged -167 .0 - 85.0) U/L; P= 0.730), medianÂ aspartate aminotransferase (AST) levels [ 43 .0 (range 14.0-297 .0)Â U/L vs 150.0 (range 24.0-840.0) U/L; P=0.081), and medianÂ gamma-glutamyl transpeptidase (GGf) levels [125.0 (48.0-481.0)Â U/L vs 235.0 (56.0-456.0) U/L; P=0.108)). Five neonates in controlÂ group died compared to two in the UDCA group (P=0.232). InÂ addition, UDCA did not significantly lengthen the survival timeÂ (hazard ratio/HR 3.62; 95%CI 0.69 to 18.77) . Conclusion Ursodeoxycholic acid tends to improve totalÂ bilirubin, direct bilirubin, and AST levels in sepsis associatedÂ cholestasis .